796 LEFT ATRIAL STRAIN ASSOCIATION WITH FUNCTIONAL CAPACITY IN CARDIAC AMYLOIDOSIS. (15th December 2022) - Pastore, Maria Concetta; Giacomin, Elisa; Marrese, Federica; Ragazzoni, Gian Luca; Mandoli, Giulia Elena; Focardi, Marta; Gozzetti, Alessandro; Cavigli, Luna; Lisi, Matteo; Valente, Serafina; D´ascenzi, Flavio; Cameli, Matteo
Abstract: Background: cardiac amyloidosis (CA) is characterized by an impairment of cardiac diastolic and, in the severe state of the disease, systolic function, with increasing worsening of functional capacity and quality of life (QoL). Six minute walking test (6MWT) and Kansas City Cardiomyopathy Questionnaire (KCCQ) are two well-known and validated methods to assess the impact of heart failure (HF) symptoms and functional capacity. Left atrial strain by speckle tracking echocardiography has emerged as an index of left ventricular (LV) diastolic function and filing pressure, and is also associated with symptoms in HF. However, its possible association with functional capacity and QoL in CA has not yet been investigated. Objectives: in this observational pilot study, our aim was to evaluate the relationship of left atrial strain with 6MWT and KCCQ in patients with CA (both AL and ATTR). Methods: we enrolled consecutive patients with CA during routine follow up visits. Patients underwent clinical and echocardiographic evaluation. On the same day, 6MWT was performed and KCCQ was administered. Speckle tracking analysis was performed offline by an experienced operator blinded to the other data. Correlation analysis was conducted using Pearsons' coefficient and linear regression analysis Results: overall, 43 patients with CA (25 ATTR, 18 AL) were enrolled. Mean age was 74 ±11, 16% (n=7) were female. Most patients showed normal left ventricular (LV) ejection fraction (55±9) and reduced LV global longitudinal strain (GLS =-12 ± 7%), 32 of them with apical sparing pattern. Mean global peak atrial longitudinal strain (PALS) was 14 (median[IQR]=6.5;23.5), mean 6MWT score = 382±104 and mean KCCQ score= 67 ± 24. Global PALS showed a strong direct correlation with 6MWT (Fig 1, P= 0.4, R 2 =0.2, p-value=0.032 ) and a trend towards correlation with KCCQ (P=0.3, p-value=0.06 ), although not reaching statistical significance, probably due to the low sample size. The correlation between PALS and 6MWT was even stronger in patients with ATTR (p=0.7, R 2 0.4; p-value<0.0001 ). Conclusions: our preliminary results show that, global PALS is associated with functional capacity and the burden of HF symptoms in ATTR and AL, suggesting its role as a more objective marker of disease severity in CA. Fig. 1